Unusual paths to local power a case of succession in Pototan and substitute candidacy in San Joaquin - Mosquera, Mae Angielee Kae T (University of the Philippines in the Visayas, 2005)
The study is a comparison of unusual path to local power. This study explored and analyzed mayoral performance in terms of programs and projects, personal traits, and factors that lead to the re-election into the mayoral office., The study was conducted in the Municipalities of Pototan and San Joaquin. Structured interview schedules were utilized to gather relevant information from six (6) key informants who have served the administrations of both the predecessor and successor or original candidate and replacement candidate. Documents from COMELEC, Sangguniang Bayan, and articles from archival research and library materials were also utilized. A one shot survey questionnaire was also distributed to the Punong Barangays in the two Municipalities. Unusual path to local power a dilemma in the successor or substitute candidate especially in the issues of legitimacy and command. The issues upon succession or substitution were the dilemma continuing or stooping the projects of the predecessor or original candidate, the peace and order situation, the subordination of the police and the cooperation of the SB members and the Punong Barangays. The issues upon succession were addressed with help and support given by the SB members and Punong Barangays. As a successor or replacement candidate, one is expected to be democratic in the implementations of programs and projects and get the support of the Municipal legislative body. Hard work, honesty, sense of dedication, and perseverance are what it takes to improve one's legitimacy. Successors or replacement candidates usually continue the programs and projects left by the predecessor or original candidate to show respect and to save municipal funds at the same time. Mayoral performance, personal traits, and political strategies are the factors that served as the base for the people to elect the successor or replacement candidate into the mayoral office. A mayor is expected to be attentive to the needs of the people through implementation of beneficial projects such as farm to market roads, construction of market, or even implementations of health related programs in the municipality. Personal traits such as friendliness, fairness, hospitability, perseverance, dedication, and honesty are the traits that subordinate officials admire in a successor.